Efficacy and Safety of Dexamethasone versus Fentanyl as an adjuvant with Bupivacaine and Lignocaine in Supraclavicular Brachial Plexus Block - Hasan, Sanjida; Chowdhury, Ahmed Abu Nasar; Khatoon, Syeda Nafisa; Barua, Kalyan; Alam, AKM Shamsul (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background: Brachial plexus blockade is gaining popularity day by day for the upper extremity surgery.Increasing the duration of local anesthetic action by adding different adjuvant is often desirable toprolong the surgical anesthesia and analgesia. The aim of this study was to make a comparative evaluationof the efficacy and safety of dexamethasone and fentanyl as an adjuvant with bupivacaine-lignocaine insupraclavicular block. Material and methods: This comparative study was carried out in the departmentof anesthesiology in Chittagong Medical College Hospital in collaboration with the department oforthopedic surgery over a period of 22months starting from July, 2012 to April, 2014. A total 130 adultpatients of either sex with American Society of Anesthesiology (ASA) health status I-II were selected forupper limb surgery under supraclavicular brachial plexus block was randomly allocated in to two groupsof 65 patients in each. Group- D was received dexamethasone 2ml (10mg) and Group-F was receivedfentanyl 2ml (100mg) in 38ml of bupivacaine and lignocaine with adrenaline (total volume of 40ml). Result: The mean onset of sensory&motor block was 7.72±1.949min & 8.75±2.008min in group-D and7.60±3.711min & 9.23±5.114min in group-F. Both the results in two group was not statistically significant(p>0.05).The duration of analgesia in group-D was 11.40±0.844hrs and in group-F was 8.62±1.747hrs.Theresults was significantly higher in group-D than group-F (p<0.05). Conclusion: There was significantlyprolonged duration of analgesia and better onset of sensory and motor block in dexamethasone groupthan in fentanyl group without any unwanted effects. JBSA 2019; 32(1): 10-17